The use of hydrotherapy as a complementary treatment for hypertension in elderly patients - Riyani, Lilis Novi; Margono, Margono; Masithoh, Robiul Fitri (Universitas Muhammadiyah Magelang, 2022)
Hypertension can cause stroke, myocardial infarction, kidney failure, and brain damage and can even cause death. Hypertension requires compliance to improve the health of one of the therapies, namely by using non-pharmacological therapy independent actions of nurses such as hydrotherapy (foot soaking in warm water), a straightforward and natural medicine because this treatment method does not have harmful side effects, and does not use drugs. Modern. This study aims to prove the effect of a warm foot soak mixed with salt and lemongrass on reducing blood pressure in hypertension. The method used in this study is a case study. This study describes a case study on nursing care at the risk of ineffective cerebral perfusion. The subject of this case study uses one respondent who does not take hypertension medication regularly, with the classification of moderate hypertension at the age of 45-65 years. Warm foot soak hydrotherapy with a mixture of salt and lemongrass can overcome the problem of the risk of ineffective cerebral tissue perfusion and reduce blood pressure. Keywords: Hypertension; elderly; community nursing; hydrotherapy; cerebral tissue perfusion